Gene polymorphism in IL17A and gene-gene interaction in the IL23R/IL17A axis are associated with susceptibility to coronary artery disease. (April 2023) - Zhang, Hongsong; Nie, Shaofang; Chen, Qianwen; Wang, Pengyun; Xu, Chengqi; Tu, Xin; Zhang, Lifang; Kenneth Wang, Qing; Zha, Lingfeng
Highlights: The first to identify the relationship between genetic variant rs2275913 in IL17A gene and early onset coronary artery disease (CAD). The minor allele C of rs6682925 in IL23R gene was associated with a decreased level of serum total cholesterol. Four genotypes (CTGG, CCAA, CCAG, CCGG) in rs6682925 and rs2275913 were significantly associated with CAD. Abstract: Aims: Studies have confirmed that the IL-23R/IL-17A axis plays an important role in the development of autoimmune and inflammatory diseases. However, its role in coronary artery disease (CAD) remains unclear. Here, we conducted a large sample case-control study to investigate the association between the IL23R/IL17A axis and CAD in the Chinese Han population. Methods: Two SNPs, rs2275913: G>A ( IL17A ) and rs6682925: T>C ( IL23R ), were genotyped in 3042 CAD cases and 3216 controls using the high-resolution melt technology (HRM). Logistic regression analyses were used to adjust the traditional risk factors for CAD and perform the gene interaction analyses. Multiple linear regression analyses were used to study the relationships between the selected SNPs and the levels of serum lipids. In addition, meta-analysis also was performed for the association between rs6682925 and rs2275913 with CAD in different popolations. Results: Our case-control and meta-analysis for single SNPs demonstrated that the frequencies of the alleles and the distribution of the genotypes had no significant differences in CAD cases compared with controls. In the stratified analysis, we observed that the frequency of the IL17A rs2275913-A allele was more epidemic in early-onset CAD than in the controls ( Pad j  = 0.005, OR = 1.209, 95% CI: 1.059–1.382), and the minor allele C of rs6682925 was associated with a decreased level of serum total cholesterol under a recessive model ( P adj  = 0.011). We demonstrated a significant interaction between rs6682925 and rs2275913 and CAD in the Chinese Han population. Four genotypes (CTGG, CCAA, CCAG, CCGG) were significantly associated with CAD ( P adj  = 2.94 × 10 −4, OR = 0.619, 95% CI: 0.478–0.803; P adj  = 0.01, OR = 1.808, 95% CI: 1.152–1.869; P adj  = 6 × 10 −6, OR = 2.179, 95% CI: 1.558–3.049; P adj  = 0.001, OR = 1.883, 95% CI: 1.282–2.762, respectively). Conclusion: Our study found no single SNP of rs2275913 in IL17A and rs6682925 in IL23R was associated with CAD in the Chinese population, but the interaction of them were significantly associated with CAD susceptibility, highlighting the key role of the IL-23R/IL-17A axis in the development of CAD. In addition, we also found rs2275913 was associated with early-onset CAD and rs6682925 was associated with total cholesterol levels, which will contribute to the clinical stratified management of this common disease.